2020
DOI: 10.1515/bot-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed resources of Korea

Abstract: AbstractKorea has a long history of utilizing seaweeds, as the country has a high biodiversity of seaweeds. The abundance and composition of seaweed species have changed over the past decades due to climate change and anthropogenic influences. Some species showed a significant extension of their distribution range to the north while some species declined. Some areas have even become barren ground. Korea has put extensive effort into restoring the seaweed resources in these defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The production of G. chorda was approximately 1769 tonnes (FW) in 2019 and increased two‐fold in 2020 6,55 . The other native Korean agarophytes Gracilaria vermiculophylla also have the potential for large‐scale cultivation, however, production still remains low compared with other seaweeds 55,56 (e.g., Pyropia , Porphyra , Undaria and Saccharina ). The key characteristics of Gracilaria aquaculture in each of the main producing countries have been depicted in Table 1.…”
Section: Global Gracilaria Aquaculture Industrymentioning
confidence: 99%
“…The production of G. chorda was approximately 1769 tonnes (FW) in 2019 and increased two‐fold in 2020 6,55 . The other native Korean agarophytes Gracilaria vermiculophylla also have the potential for large‐scale cultivation, however, production still remains low compared with other seaweeds 55,56 (e.g., Pyropia , Porphyra , Undaria and Saccharina ). The key characteristics of Gracilaria aquaculture in each of the main producing countries have been depicted in Table 1.…”
Section: Global Gracilaria Aquaculture Industrymentioning
confidence: 99%
“…The CHCl 3 -soluble portion was mixed with the EtOAc-soluble portion due to their similar HPLC profiles. The combined extract was subjected to medium-pressure liquid chromatography (MPLC) eluting with ACN/H 2 O (10:90 to 100:0) to obtain sub-fractions (1)(2)(3)(4)(5)(6). Sub-fraction 1 was further separated by MPLC, followed by semi-HPLC eluting with 30% ACN in water to give compound 1 (2.0 mg).…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…1 Sargassum micracanthum (Kutzing) Endlicher is a member of the family Sargassaceae, which comprises about 193 species. 2 The species has a coriaceous thallus up to 50 cm in length and grows on rocks in the low intertidal to upper subtidal zones of open coasts. 3 Previous studies have reported that Sargassum species contain compounds with various biological activities, such as anti-oxidative, cholinesterase inhibitory, neuroprotective, anti-cancer, anti-inflammatory, and anti-viral activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The project focuses on deploying concrete artificial reefs in areas with low urchin density (Jeon et al, 2015) in combination with juvenile kelp transplants, seeding (spore bags), and/or urchin removal, and subsequent monitoring. As of 2019, reefs and transplants were deployed over an area of approximately 21,489 ha (Park et al, 2019;Hwang et al, 2020) with a survival rate of ∼50% (Jeon, 2019, personal communication). Artificial reefs were originally used because the agency believed that transplanting kelp onto rock covered by crustose coralline algae would limit success, but new methods are being developed to deploy transplants onto natural rocky reefs.…”
Section: Marine Restoration Program Koreamentioning
confidence: 99%